2021
DOI: 10.1038/s41467-021-23329-z
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mature compact ventricular cardiomyocytes from human pluripotent stem cells

Abstract: Compact cardiomyocytes that make up the ventricular wall of the adult heart represent an important therapeutic target population for modeling and treating cardiovascular diseases. Here, we established a differentiation strategy that promotes the specification, proliferation and maturation of compact ventricular cardiomyocytes from human pluripotent stem cells (hPSCs). The cardiomyocytes generated under these conditions display the ability to use fatty acids as an energy source, a high mitochondrial mass, well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 70 publications
2
103
0
Order By: Relevance
“…It was shown that the proliferative effect of proepicardial cells on co-cultured ventricular cardiomyocytes was mediated at least in part by RA-dependent IGF2 signaling (Tan et al, 2021). IGF2 has also been utilized for the maturation of compact ventricular cells derived from hPSCs (Funakoshi et al, 2021). IGF2 was strongly decreased in both Raldh2 À/À and Rxra mutants and is implicated in ventricu-lar wall proliferation (Brade et al, 2011;Li et al, 2011).…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…It was shown that the proliferative effect of proepicardial cells on co-cultured ventricular cardiomyocytes was mediated at least in part by RA-dependent IGF2 signaling (Tan et al, 2021). IGF2 has also been utilized for the maturation of compact ventricular cells derived from hPSCs (Funakoshi et al, 2021). IGF2 was strongly decreased in both Raldh2 À/À and Rxra mutants and is implicated in ventricu-lar wall proliferation (Brade et al, 2011;Li et al, 2011).…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…Furthermore, in the developing heart, it is well known that there are two distinct subpopulations in the ventricle: trabecular and compact cardiomyocytes. Recent reports demonstrated the successful generation of trabecular and compact ventricular PSC cardiomyocytes by manipulating neuregulin and Wnt signaling, respectively (Mikryukov et al 2021 ; Funakoshi et al 2021 ). The specified ventricular cardiomyocytes would be helpful to analyze trabeculation- and compaction-related diseases, such as LV non-compaction.…”
Section: Recent Progresses On Quality Of Ipsc-derived Cells For Disease Study and Treatmentmentioning
confidence: 99%
“…We recently developed an efficient maturation protocol using the combination of T3, Dex, PPARα agonist, and palmitate in low glucose-containing media. The PSC cardiomyocytes treated by this protocol showed structural maturation, withdrawal from the cell cycle, and the ability to utilize exogenous fatty acids efficiently as an energy source, which is one of the representative features of the adult-like metabolism in the heart (Funakoshi et al 2021 ). In addition to these factors, Sakamoto et al demonstrated that ERR signaling plays an essential role in postnatal cardiac maturation in mice (Sakamoto et al 2020 ).…”
Section: Recent Progresses On Quality Of Ipsc-derived Cells For Disease Study and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches were attempted to overcome the issue of hiPSC-CMs immaturity, such as the long-term culture [46,47], the use of hormones [48], metabolic substrates [49,50] and microRNAs [51]. Recently, it has been observed that inhibition of the mechanistic target of the rapamycin (mTOR) pathway enhances hiPSC-CMs maturation by shifting cells to a quiescent state, which enhances cardiomyocyte maturity.…”
Section: Strategies For Hipsc Differentiation Into Mature Cardiomyocytesmentioning
confidence: 99%